Personalized Human Astrocyte‐Derived Region‐Specific Forebrain Organoids Recapitulate Endogenous Pathological Features of Focal Cortical Dysplasia - Jinhong Xu; Yufei Kong; Nawen Wang; Huijuan Li; Yunteng Li; Zhuo Liu; Yuling Yang; Xiao Yu; Huihui Liu; Jing Ding; Yi Wang; Rui Zhao; et al. (Advanced Science)
Abstract Focal cortical dysplasia (FCD) is a highly heterogeneous neurodevelopmental malformation, the underlying mechanisms of which remain largely elusive. In this study, personalized dorsal and ventral forebrain organoids (DFOs/VFOs) are generated derived from brain astrocytes of patients with FCD type II (FCD II). The pathological features of dysmorphic neurons, balloon cells, and astrogliosis are successfully replicated in patient‐derived DFOs, but not in VFOs. It is noteworthy that cardiomyocyte‐like cells correlated with dysmorphic neurons are generated through the high activation of BMP and WNT signaling in some of the FCD‐organoids and patient cortical tissues. Moreover, functional assessments demonstrated the occurrence of epileptiform burst firing and propagative self‐assembling neuronal hyperactivity in both FCD‐DFOs and VFOs. Additionally, the heterotopic cardiomyocyte‐organoids demonstrated the capacity for cardiomyocyte contraction and rhythmic firing. The presence of these cardiomyocytes contributes to the hyperactivity of neural networks in cardioids‐DFOs assembly. In conclusion, the personalized region‐specific forebrain organoids derived from FCD patient astrocytes effectively recapitulate heterogeneous pathological features, offering a valuable platform for the development of precise therapeutic strategies.